2016
DOI: 10.1016/j.mgene.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity estimates point to immediate efforts for conserving the endangered Tibetan sheep of India

Abstract: Tibetan is a valuable Himalayan sheep breed classified as endangered. Knowledge of the level and distribution of genetic diversity in Tibetan sheep is important for designing conservation strategies for their sustainable survival and to preserve their evolutionary potential. Thus, for the first time, genetic variability in the Tibetan population was accessed with twenty five inter-simple sequence repeat markers. All the microsatellites were polymorphic and a total of 148 alleles were detected across these loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 30 publications
3
41
1
1
Order By: Relevance
“…Selection of R genederived markers with a range of polymorphisms may reduce the risk of overestimating genetic variability. This is in agreement with a study on genetic diversity using microsatellite markers in sheep as reported by Sharma et al (2016).…”
Section: Discussionsupporting
confidence: 93%
“…Selection of R genederived markers with a range of polymorphisms may reduce the risk of overestimating genetic variability. This is in agreement with a study on genetic diversity using microsatellite markers in sheep as reported by Sharma et al (2016).…”
Section: Discussionsupporting
confidence: 93%
“…As part of this program, the present study was undertaken with the objectives of evaluating diversity and genetic relationship of five economically important sheep breeds of Pakistan, Balkhi, Damani, Kaghani, Salt Range and Thalli. The results of the present work will help to better understand the current genetic diversity in these breeds, and contribute towards formulating effective strategies for prioritization, conservation and genetic improvement of indigenous sheep breeds in Pakistan (Gaouar et al, 2015;Guang-Xin et al, 2016;Sharma et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Paiva et al (2011b) used US and Brazilian datasets and determined F IS values ranging from -10.7% and 32.6%. Such heterozygote deficiency has been observed in Indian breeds, including Magra (15.9%) (Arora & Bhatia, 2006), Muzzafarnagri (5.8%) (Arora & Bhatia, 2004), Shahabadi (21.5%) (Panday et al, 2010), Tibetan (30.2%) (Sharma et al, 2016), Vembur (29.4%) (Pramod et al, 2009), Sarda sheep from Italy (19%) (Pariset et al, 2003) and 29 European sheep breeds (mean of 12.1%) (Lawson Handley et al, 2007).…”
Section: Resultsmentioning
confidence: 98%